Frequency analysis in fault detection of dual‐channel BLDC motors with combined star–delta winding. Issue 7 (11th March 2021) - Korkosz, Mariusz; Prokop, Jan; Pakla, Bartłomiej; Bogusz, Piotr
Abstract: This study compares the properties of dual‐channel brushless DC motors with permanent magnets (DCBLDCMs) in three configurations of the stator windings of both channels. An analysis was performed of star‐connected (Y), delta‐connected (Δ), and combined star–delta (YΔ) channel windings. A proprietary mathematical model of a DCBLDCM machine with combined star–delta windings is presented. Each type of winding configuration was evaluated in terms of tolerance to the occurrence of a discontinuity in the channel. An Fast Fourier Transform (FFT) analysis of the selected voltage signal was used to diagnose the operating status of the DCBLDCM. It was demonstrated that it provides unambiguous information about the operating status of individual channels of the motor. In the case od 24/10 DCBLDCM design, the harmonic spectra of a selected voltage signal in relation to the artificial neutral point, are presented. The results of simulation tests were compared with the results of laboratory measurements. It was demonstrated that an FFT analysis of a voltage signal in relation to the artificial neutral point identifies a fault in a channel of the motor. When evaluating the characteristics of individual winding configurations, the value of electromagnetic torque, torque ripple, system efficiency, and emitted noise were taken into account. In the conclusions, the advantages of the combined star–delta winding compared to the traditional star and delta winding configurations are presented.